ANISOTROPIC MIGRATION WEIGHT FOR AMPLITUDE-PRESERVING MIGRATION AND SENSITIVITY ANALYSIS - Kiyashchenko D.; Kashtan B.; Plessix R.-E. (My University, 2004)
An amplitude-preserving anisotropic migration formula is derived in this paper. The migration is viewed as a weighted diffraction stack and the migration weights are estimated with the stationary phase theorem. To obtain a formula easy to implement, the weights are written in terms of quantities computable along the rays. A sensitivity analysis is then carried out to show that, in the vertical transverse isotropic case, the amplitude-preserving migration is mainly governed by two parameters: the anisotropic NMO velocity and the parameter eta. These parameters can be estimated from the data with a velocity (background) analysis. Therefore, it is possible to use this amplitude-preserving anisotropic migration to recover the correct amplitudes versus offset or azimuth in the migrated image.
Keywords: anisotropy; migration weights; ray tracing